Development of STEM-Based E-LKPD on Senses System Material to Improve Creative Thinking Ability - Sri Yanti Tarihoran; Nirwana Anas (Jurnal Penelitian Pendidikan IPA, 2023)
Creative thinking is an important problem in learning. One of the learning approaches that can be used to improve creative thinking skills is the STEM learning approach. This is effective if it is supported by teaching materials in the form of E-LKPD. This study aims to determine the development of STEM-based E-LKPD learning media on human sensory material to improve the creative thinking skills of class XI students at SMA/MA. The method used in this study uses the Research and Development (R&D) method with a 4D model. The results of data analysis were carried out using a validation sheet in the form of a response questionnaire. The validation results from media experts get a percentage of 80% in a very valid category, from material experts get a percentage of 97% in a very valid category, from question instrument experts get a percentage of 88% in a very valid category and from questionnaire experts get a percentage of 100% with very valid category. The practicality test obtained a percentage score of 100% from school teachers in the very practical category and 98.2% from students in the very practical category. The N-Gain results in this study obtained a value of 0.6 in the moderate category. The conclusion of this study states that the STEM-based electronic Student Worksheet (e-LKPD) is very valid, practical and effective